A Matter of Trust: The Role of Communities in Energy Decision-Making - Cleland, Michael (Université d'Ottawa | University of Ottawa, 2016)
Energy development sometimes faces powerful local opposition in communities across Canada. Energy companies have found themselves under the microscope and regulators have been forced to confront their evolving role in this new context. Our new research shows, however, that the nature of this opposition, and the underlying concerns, are often not what opinion leaders and political decision-makers have assumed. Importantly, local opposition is not restricted to pipelines and oil sands, and it is often not about climate change. This is the second and final report from a project designed to understand what drives community confidence in energy project decision-making processes. The project aims to: develop a better understanding of the relationship between local communities and public authorities in energy development; identify reasons for shortcomings; and develop ideas for restoring that trust and confidence.
Keywords: Public confidence; Social acceptance; Renewable energy; Energy policy; Oil and Gas; Polarization; Social licence; Energy Projects; Community engagement; Public Participation; Climate change; Regulation; Canada